Still missing [large type] - Stevens, Chevy (Thorndike Press large print core, 2010)
On the day she was abducted, Annie O'Sullivan, a 32-year-old realtor, had three goals--sell a house, forget about a recent argument with her mother, and be on time for dinner with her boyfriend. The open house is slow, but when her last visitor pulls up in a van as she's about to leave, Annie thinks it just might be her lucky day after all. Interwoven with the story of the year Annie spent as the captive of a psychopath in a remote mountain cabin, which unfolds through sessions with her psychiatrist, is a second narrative recounting events following her escape--her struggle to piece her shattered life back together and the ongoing police investigation into the identity of her captor.